Effect of the consumption of lean red meat from beef (pirenaica breed) versus lean white meat (chicken) on the gut microbiota: a randomized cross-over study in healthy young adults - Rueda-De Torre, Isabel; Plaza-Diaz, Julio; Miguel-Berges, María L.; Gil, Ángel; Grasa, Laura; Esteban, Luis Mariano; Sabroso-Lasa, Sergio; Campo, María M.; Santolaria, Pilar; Moreno, Luis A.; Santaliestra-Pasías, Alba M. (Molecular nutrition & food research, 2025)
Limited evidence exists regarding the impact of meat consumption on the human gut microbiota, with factors such as animal source, production system, and cooking methods often overlooked. This study evaluates the effect of Pirenaica breed beef or conventional chicken-based diets on the gut microbiota of healthy adults. A randomized cross-over controlled trial with two 8-week periods, separated by a 5-week washout, is carried out. Participants consume either Pirenaica breed beef or chicken three times per week with their diet. Stool samples are collected at the beginning and end of each period. Gut microbiota is analyzed via amplification and sequencing of V3–V4 regions of 16S rRNA. Alpha diversity and relative abundances at phylum and genus levels are calculated. Sixteen participants are included (mean age 20.12 ± 2.36 years). Both diets induce modest changes inmicrobial composition, with no significant differences between groups. At the phylum level, Bacillota increased, while Synergistota, Chloroflexota, and Pseudomonadota decreased. Alpha diversity parameters declined significantly after the chicken-based diet, although overall reduction in microbial diversity was observed across both interventions. The consumption of lean red meat or lean white meat as part of habitual diet produces similar effects on the gut microbiota.
Keywords: diet intervention; gut microbiota; red meat; white meat; young adults